A single-ion gel polymer electrolyte based on polyimide grafted with lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide for high performance lithium ion batteries. Issue 4 (5th January 2023) - Li, Zhangnan; Liu, Yuhan; Liang, Xiaoxiao; Yu, Mengxuan; Liu, Baijun; Sun, Zhaoyan; Hu, Wei; Zhu, Guangshan
Abstract : A polyimide-based single-ion polymer PI-LiCPSI was prepared. PI-SIGPE obtained by compounding of PI-LiCPSI and PVDF-HFP showed good mechanical properties due to the rigid frame and strong interface, and also possessed excellent electrochemical and cycling performance. Abstract : With a high lithium-ion transfer number ( t Li + ), single-ion gel polymer electrolytes can inhibit the growth of lithium dendrites and improve cycling performance effectively, and have attracted much attention. Due to high thermal stability, hydroxyl-containing polyimide (PI-OH) was prepared to be applied as the backbone, and grafted with lithium 3-chloropropanesulfonyl(trifluoromethanesulfonyl)imide (LiCPSI) to synthesize the single-ion polymer (PI-LiCPSI), which was further compounded with poly(vinylidene fluoride)-(hexafluoropropylene) (PVDF-HFP) to obtain polyimide single-ion polymer electrolyte (PI-SIPE). Its shrinkage rate was only about 0.3% after being kept at 200 °C for 0.5 h. And the tensile strength and Young's modulus were 30 MPa and 1.72 GPa, respectively, due to the rigid PI main chain and the strong interface between PVDF-HFP and PI-LiCPSI. The PI-SIGPE obtained by addition of EC/DMC into PI-SIPE presented both excellent ion transport capacity and electrochemical stabilities, with a high ( t Li + ) (0.97), a wide electrochemical window (5.2 V), and an ionic conductivity of 1.4 × 10 −4 S cm −1 at 30 °C. The initial discharge capacity of the Li/PI-SIGPE/LFP battery can be as high as 161 mA h g −1 at 0.2C, and the capacity retention rate was more than 90% after 330 cycles. Predictably, PI-SIGPEs with superior synthetic performances have great application prospects in solid state lithium ion batteries (SSLIBs).